Extension of the content, functionality and usability of the online FSK‐Web model repository. Issue 12 (20th December 2021) - Schüler, Thomas; Ganas, Petra; Fuhrmann, Marcel; de Alba Aparicio, Miguel; Lopez de Abechuco, Estibaliz; Mensching, Yvonne; Valentin, Lars; Filter, Matthias
Abstract: In December 2016 EFSA and BfR stepped into a Framework Partnership Agreement (FPA) to work jointly on the development, improvement and dissemination of global food safety tools. As outlined in the Specific Agreement #7 of this FPA one specific objective was to work towards the development of a fully operational online model repository that includes features to create, upload, download and execute models with user‐defined inputs for the predefined model parameters. The user interface of the so‐called FSK‐Web model repository had to be designed such, that it is user‐friendly and usable on various end‐user devices and web browser software. The developed "FSK‐Web 1.0" platform now even contains additional services, e.g. to link models with EFSA's Knowledge Junction (KJ) or to join up to four models in a graphical user‐interface (GUI) online. Detailed manuals, video tutorials and an online e‐learning course were developed to support the use of the FSK‐Web repository. A repository disclaimer and a model curation policy were drafted and will be released after being agreed with EFSA. The project created three key outcomes: (1) an operational curated web‐based food safety model repository, and a significant number of executable QMRA models in FSKX format relevant for risk assessment; (2) improved usability and annotation of the various services offered by the FSK‐Web model repository including manuals and online resources explaining the functionality and use of all aspects of the model repository; (3) provision of the possibility to link different FSKX models to create new combined models, including the option to combine models programmed in different scripting languages (also execution of combined R / Python models supported).